2020
DOI: 10.3390/diagnostics11010048
|View full text |Cite
|
Sign up to set email alerts
|

MMP-7 Serum and Tissue Levels Are Associated with Poor Survival in Platinum-Treated Bladder Cancer Patients

Abstract: Chemotherapy resistance is a main cause of therapeutic failure and death in bladder cancer. With the approval of immune checkpoint inhibitors, prediction of platinum treatment became of great clinical importance. Matrix metalloproteinase-7 (MMP-7) was shown to be involved in cisplatin resistance. Therefore, tissue and circulating MMP-7 levels were evaluated in 124 bladder cancer patients who received postoperative platinum-based chemotherapy. Tissue MMP-7 levels were analyzed by immunohistochemistry in 72 form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…As MMP-7 has been shown to be able to proteolytically cleave membrane bound PD-L1 and we formerly measured serum MMP-7 concentrations in samples of patients treated with adjuvant chemotherapy ( n = 23) [ 17 ]. Here, we performed the Spearmen´s rank correlation analysis between sPD-L1 and MMP7, which revealed a significant positive correlation between the concentrations of these two proteins (rs = 0.525, p = 0.001) ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As MMP-7 has been shown to be able to proteolytically cleave membrane bound PD-L1 and we formerly measured serum MMP-7 concentrations in samples of patients treated with adjuvant chemotherapy ( n = 23) [ 17 ]. Here, we performed the Spearmen´s rank correlation analysis between sPD-L1 and MMP7, which revealed a significant positive correlation between the concentrations of these two proteins (rs = 0.525, p = 0.001) ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Serum MMP-7 levels were measured using the Quantikine ELISA kit from R&D Systems (Cat.Nr. : DMP700) and published in previous work of our group [ 17 ]. To exclude a possible interference/cross reactivity between the therapeutic anti-PD-L1 antibody (atezolizumab, Tecentriq®, Roche, Basel, Suisse) and our ELISA kit, we performed an ELISA analysis with atezolizumab and pembrolizumab.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a handful of possible molecular mechanisms that may explain this suboptimal response to cytotoxic chemotherapy. Recent studies have revealed that UC patient differences in the expression of various proteins, such as matrix metalloproteinase-7 and syndecan-1, affect the prognosis following chemotherapy ( 7 , 8 ). Additionally, individual variations in tumor-infiltrating B-cell activity have significant prognostic value for MIBC patients ( 9 ), and long noncoding mRNAs have also been found to regulate muscle-invasive UC proliferation and resistance to chemotherapy ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, relapse after radical cystectomy or advanced conditions is involved in the poor outcomes of patients [ 2 ]. Chemotherapy and surgery are the main treatment strategies for BC, and can effectively prolong the survival of patients with BC [ 3 ]. Unfortunately, almost of patients with advanced conditions will die from BC.…”
Section: Introductionmentioning
confidence: 99%